Adolescents' perceptions of sexual wellbeing - Olsson, Emeli (Department of Social Development, 2023)
This study explored adolescents' personal understanding of sexual wellbeing among young people aged 16-19 in Langa, Cape Town. The study further explored the participants' understanding of possible promoting and inhibiting factors to sexual wellbeing in their interpersonal and societal context. Twenty participants were selected using purposive sampling. In depth, face-to-face interviews were conducted using a semi-structured interview guide with open-ended questions. The data was analysed using qualitative research methods. The study revealed the complex nature of sexual wellbeing and how adolescents understand sexual wellbeing in a multi-faceted sense from individual, interpersonal, and societal levels. The most prominent factors of sexual wellbeing on an individual level were identified as maturity, sexual self-concept, sexual orientation, gender identity, and sexual experience. On an interpersonal level the participants identified safer sex practices and consent as important factors of sexual wellbeing. From a societal level, different forms of sexuality knowledge and to be free from discrimination were emphasised. The findings further revealed factors that may promote or inhibit sexual wellbeing in the participants' interpersonal and societal context. The participants identified that communication about sex and sexuality in the family had the potential to promote or inhibit sexual wellbeing. Peer pressure, school sexuality education, and how facilitators at their after-school activity approach sex and sexuality discussions could influence the participants' perceptions of sexual wellbeing. The participants further found that their communities and different forms of media had the potential to influence sexual wellbeing in adolescence. The participants did not perceive themselves as having sexual wellbeing at the moment but discussed several promoting strategies for sexual wellbeing. The participants argued for the importance of positive and supportive communication in their households, and the researcher recommended to further investigate strategies to support caregivers in this role. The participants recommend an improvement of school sexuality education and sexuality information provided at their after-school activities. The researcher supported this recommendation by suggesting comprehensive sexuality education in schools and after-school activities, together with further research into sex-positive approaches to prevention programmes and promoting sexual wellbeing in adolescence.